Evaluation of the Phenolic Components, Fiber Content, Antioxidant Activity, and Prebiotic Capacity of a Shortbread Cookie Fortified with Hazelnut Skin Waste - Lara Costantini; Giacomo Di Matteo; Martina Felli; Daniel V. Savatin; Luisa Mannina; Nicolò Merendino (Foods)
Food reformulation is a strategy to make healthier foods by using food waste matrices that are still nutritionally valid. A shortbread cookie was reformulated replacing hazelnut skin (HS) of the Tonda Gentile Romana variety (5% and 10%) to refined flour and proportionally decreasing the butter amount. This resulted in significant, two- and five-fold, increases in the antioxidant capacity compared with the control, in the 5% and 10% fortified recipes, respectively. Among the most important antioxidants, gallic acid, catechin, phloridzin, and protocatechuic acid were found. Moreover, here we found, for the first time, that HS from the Romana variety had a high total fiber content (44.13 g/100 g), most of which was insoluble fiber. Therefore, HS 10% addition to the shortbread cookie recipe caused a significant increase in fiber content, making the experimental cookie earn the nutritional claim of “high fiber content”. Finally, preliminary evidence demonstrated that 10% HS, in comparison to 5%, following in vitro upper gastrointestinal digestion, conferred significant prebiotic activity in an in vitro culture of L. rhamnosus. Therefore, from the perspective of the circular economy, HS could be a valuable ingredient to increase the antioxidant and prebiotic activities of conventional foods.